2012
DOI: 10.5650/jos.61.377
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of Bioactive Sophorolipids by Starmerella bombicola NRRL Y-17069 by Design of Experiment Approach with Successive Purification and Characterization

Abstract: INTRODUCTION Biosurfactants are potential surfactants obtained from natural sources and gives several advantages over chemically synthesized surfactants. They are less toxic in nature, biodegradable and environmentally acceptable 1) and hence attracted a great attention. SLs, surface-active glycolipids are one of the well-known members of biosurfactant family produced by microorganisms and extracellularly by Candida bombicola 2-5). These are amphiphilic in nature, i.e. containing both hydrophobic as well as hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
7
11
0
Order By: Relevance
“…All these structural details of the products were found similar to those reported by Yongmei and Lu-Kwang (2001); Daverey and Pakshiragan (2009) and Bajaj et al (2012), which confirmed that these products are SL compounds.…”
Section: Ft-ir Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…All these structural details of the products were found similar to those reported by Yongmei and Lu-Kwang (2001); Daverey and Pakshiragan (2009) and Bajaj et al (2012), which confirmed that these products are SL compounds.…”
Section: Ft-ir Analysissupporting
confidence: 88%
“…The presence of the-CO-CH 3 group in all structures was confirmed by the signals at 2.06 ppm in the spectra; on the other hand, the protons of two glucose were resonated at 3.4≈4.3 ppm in the Hexane fraction (E III). The signals obtained were similar to the one in the 1 H NMR spectrum of the SL compounds reported by other researchers (Wei et al, 2005;Chen et al, 2006a;Gao et al, 2007;Pakshiragan 2009 andBajaj et al, 2012).…”
Section: H Nmr Analysissupporting
confidence: 87%
“…Substrates In all the previous sophorolipid studies 14,28 , hexane was used as solvent to remove unused residual oil. This study reveals that castor oil and sophorolipids both are insoluble in hexane.…”
Section: Discussionmentioning
confidence: 99%
“…The residue was further washed twice with hexane to remove the residual oil. The total yield of these partially purified SLs was measured by gravimetric measurement 14 The presence of ricinoleic fatty acids in sophorolipids was confirmed by GC analysis and results were compared with methyl ester of castor oil by GC. The samples were hydrolysed and esterified by adding 0.4 ml of 20 mM cupric acetate monohydrate in methanol and 2 ml of 0.5 N HCl in Hydranal.…”
Section: Estimation Identi Cation and Characterization Of Slsmentioning
confidence: 99%
See 1 more Smart Citation